2021
DOI: 10.1177/08948453211043878
|View full text |Cite
|
Sign up to set email alerts
|

Work Values and Job Satisfaction: The Mediating Role of Basic Psychological Needs at Work

Abstract: This study investigated the mediating role of basic psychological needs at work in the association from work values to job satisfaction. Using a four-factor model of work values, we tested how each work value factor was related to basic psychological need satisfaction and frustration at work. The sample included 228 workers (72% female) surveyed twice over a 7-week interval. Results showed that need satisfaction at work was positively predicted by intrinsic and social work values and negatively predicted by ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
(85 reference statements)
6
21
0
1
Order By: Relevance
“…Specifically, types of values can be distinguished based on their association with PNS and PNF (Vansteenkiste et al, 2007;Vansteenkiste & Ryan, 2013). This distinctfion was also made for work values in previous studies, which showed that intrinsic and social work values were positively related to PNS at work and negatively to PNF at work, whereas extrinsic and status work values were positively associated to PNF at work and negatively to PNS at work (Busque-Carrier et al, 2021b;Schreurs et al, 2014;Vansteenkiste et al, 2007;Zhang et al, 2019). Some studies examined the association of work values with PNS by creating a score that represent the relative contribution of one value factor, to partially control the contribution of other factors.…”
Section: A Self-determination Perspective On Valuesmentioning
confidence: 71%
See 1 more Smart Citation
“…Specifically, types of values can be distinguished based on their association with PNS and PNF (Vansteenkiste et al, 2007;Vansteenkiste & Ryan, 2013). This distinctfion was also made for work values in previous studies, which showed that intrinsic and social work values were positively related to PNS at work and negatively to PNF at work, whereas extrinsic and status work values were positively associated to PNF at work and negatively to PNS at work (Busque-Carrier et al, 2021b;Schreurs et al, 2014;Vansteenkiste et al, 2007;Zhang et al, 2019). Some studies examined the association of work values with PNS by creating a score that represent the relative contribution of one value factor, to partially control the contribution of other factors.…”
Section: A Self-determination Perspective On Valuesmentioning
confidence: 71%
“…Therefore, examining the unique contribution of each psychological need could improve our understanding of their association with work values. However, status work values in the FFM-WV was previously shown to be unrelated to PNS at work and to contribute positively to PNF at work (Busque-Carrier et al, 2021b).…”
Section: Implications For Theories and Researchmentioning
confidence: 89%
“…Results from a study on teaching motivation of junior scientists at universities show that basic need satisfaction-satisfaction of the need for autonomy in particular-was associated with the occurrence of goal conflict and the experience of psychological strain due to goal conflict, whereas satisfaction of the basic need for competence was associated with autonomous teaching motivation (Esdar et al, 2016). Therefore, we propose that the negative relationship between conflicting goals and lower self-determined motivation is mediated by the satisfaction of basic psychological needs Busque-Carrier et al, 2021), in particular, by diminishing perceptions of autonomy and competence.…”
Section: The Present Study: How Goal Conflicts May Affect Teaching Mo...mentioning
confidence: 82%
“…The three basic needs postulated within the SDT framework encompass the need to experience oneself as agentic and autonomous (basic need for autonomy), the need to experience oneself as successful at challenging tasks and competent in attaining desired outcomes (basic need for competence), and the need to experience oneself as socially connected to other people (basic need for relatedness; Deci and Ryan, 2000;Roth, 2014). Previous research from other contexts has shown that the satisfaction of basic needs can act as a mediator between (the attainment of) goals and work values on the one hand and measures of (job) satisfaction and wellbeing on the other hand Busque-Carrier et al, 2021).…”
Section: Teaching Motivation From a Self-determination Theory Perspec...mentioning
confidence: 99%
“…In another study, work needs, work attitudes (internal and external satisfaction, organizational and professional commitment), and professional preferences were compared in a sample of male accountants at different career stages, and significant differences were obtained (Adler & Aranya, 1984). In a similar context, psychological needs were associated with variables such as career commitment (Baluku et al, 2020) and work values (Busque-Carrier et al, 2021).…”
Section: Needs and Occupational Preferencementioning
confidence: 99%